Modification Strategy of D-leucine Residue Addition on a Novel Peptide from Odorrana schmackeri, with Enhanced Bioactivity and In Vivo Efficacy - Aifang Yao; Yingxue Ma; Xiaoling Chen; Mei Zhou; Xinping Xi; Chengbang Ma; Shen Ren; Tianbao Chen; Chris Shaw; Lei Wang (Toxins, 2021)
Brevinins are a well-characterised, frog-skin-derived, antimicrobial peptide (AMP) family, but their applications are limited by high cytotoxicity. In this study, a wild-type des-Leu2 brevinin peptide, named brevinin-1OS (B1OS), was identified from Odorrana schmackeri. To explore the significant role of the leucine residue at the second position, two variants, B1OS-L and B1OS-D-L, were designed by adding L-leucine and D-leucine residues at this site, respectively. The antibacterial and anticancer activities of B1OS-L and B1OS-D-L were around ten times stronger than the parent peptide. The activity of B1OS against the growth of Gram-positive bacteria was markedly enhanced after modification. Moreover, the leucine-modified products exerted in vivo therapeutic potential in an methicillin-resistant Staphylococcus aureus (MRSA)-infected waxworm model. Notably, the single substitution of D-leucine significantly increased the killing speed on lung cancer cells, where no viable H838 cells survived after 2 h of treatment with B1OS-D-L at 10 μM with low cytotoxicity on normal cells. Overall, our study suggested that the conserved leucine residue at the second position from the N-terminus is vital for optimising the dual antibacterial and anticancer activities of B1OS and proposed B1OS-D-L as an appealing therapeutic candidate for development.